FEMINISME DALAM NOVEL JALAN BANDUNGAN KARYA NH.DINI - Devita Devita; Parlindungan Nadeak; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was motivated by the issue of injustice against women which is often an interesting topic of discussion in a novel. A common problem in this research was the form of injustice against women in the novel Jalan Bandungan by Nh. Dini. The purpose of this study was to describe the problem discussed while the benefits in this study can be used as a basis for further research, especially in the field of literature feminism studies. The theory used in this study was the structure of the novel builder, the nature of feminists, feminist literary criticism, feminist development and diversity, forms of injustice against women, forms of women's resistance, profeminism and contrafeminism attitudes, people's views of women, women's position, literary learning in high school.  Keywords: Bandungan, Feminism, Nh.Dini.